Linguistic style as a digital marker for depression severity: an ambulatory assessment pilot study in patients with depressive disorder undergoing sleep deprivation therapy - Hartnagel, Lisa-Marie; Ebner-Priemer, Ulrich; Foo, Jerome Clifford; Streit, Fabian; Witt, Stephanie; Frank, Josef; Limberger, Matthias F.; Horn, Andrea B.; Gilles, Maria; Rietschel, Marcella; Sirignano, Lea (Acta psychiatrica Scandinavica, 2025)
Background Digital phenotyping and monitoring tools are the most promising approaches to automatically detect upcoming depressive episodes. Especially, linguistic style has been seen as a potential behavioral marker of depression, as cross-sectional studies showed, for example, less frequent use of positive emotion words, intensified use of negative emotion words, and more self-references in patients with depression compared to healthy controls. However, longitudinal studies are sparse and therefore it remains unclear whether within-person fluctuations in depression severity are associated with individuals' linguistic style. Methods To capture affective states and concomitant speech samples longitudinally, we used an ambulatory assessment approach sampling multiple times a day via smartphones in patients diagnosed with depressive disorder undergoing sleep deprivation therapy. This intervention promises a rapid change of affective symptoms within a short period of time, assuring sufficient variability in depressive symptoms. We extracted word categories from the transcribed speech samples using the Linguistic Inquiry and Word Count. Results Our analyses revealed that more pleasant affective momentary states (lower reported depression severity, lower negative affective state, higher positive affective state, (positive) valence, energetic arousal and calmness) are mirrored in the use of less negative emotion words and more positive emotion words. Conclusion We conclude that a patient's linguistic style, especially the use of positive and negative emotion words, is associated with self-reported affective states and thus is a promising feature for speech-based automated monitoring and prediction of upcoming episodes, ultimately leading to better patient care.
Heft 3 ist die Sonderausgabe "Digital psychiatry"
Erstmals veröffentlicht: 10. Juli 2024
Gesehen am 03.02.2025